Students' Critical Thinking Dispositions: Truth Seeking and Systematic - Syamsulrizal; Supratman; Sahidi (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
This study aims to describe students’ critical thinking dispositions in the aspects of truth-seeking and systematic thinking in mathematical problem-solving. This research employed a qualitative descriptive design involving two ninth-grade students selected through purposive sampling based on high mathematical ability. Data were collected through problem-solving tasks and semi-structured interviews and analyzed using indicators of truth-seeking (identifying relevant information, evaluating assumptions, and using accurate data) and systematic thinking (organizing solution steps logically, using appropriate mathematical notation, and verifying results). Data validity was ensured through triangulation of written responses and interview data. The findings reveal that students are generally able to organize relevant data, follow logical procedures, and obtain correct answers, indicating the presence of procedural-level critical thinking dispositions. However, students demonstrate weaknesses in verifying assumptions and evaluating final results, showing that reflective aspects of critical thinking are not yet fully developed. These findings highlight a gap between procedural competence and the depth of critical thinking dispositions, where correct answers do not necessarily reflect strong critical thinking. This study contributes theoretically by emphasizing that critical thinking involves not only cognitive skills but also reflective habits that require explicit development. Practically, the results suggest the need for instructional strategies that encourage students to recheck their work, question assumptions, and reflect on their reasoning processes.